(untitled)
A megalonychid mandibular portion coming from tbe Mio-Pliocene deposits of tbe Entre Ríos Province is described. Frorn this analysis, the following conclusions are obtained: a) the fossil remain belongs to a new taxon, wich í s namecl Paranabradys vucetichae n. gen., n. sp.; b) thís Tardígrada is relatecl to many other extinct forms (Ottotherium. ancl Menilaus